2022
DOI: 10.1111/acfi.12958
|View full text |Cite
|
Sign up to set email alerts
|

12 years of integrated reporting: A review of research

Abstract: Corporate reporting provides insights into how a company views itself and its role in society by communicating the company's performance in both financial and non-financial terms (Krzus, 2011). Growing business complexity and the globalised business environment have increased pressure on companies to be more transparent in reporting their business performance and value propositions by adopting a forward-looking approach, which led to the evolution of integrated reporting (IR) as a new corporate reporting refor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 226 publications
(601 reference statements)
0
10
0
Order By: Relevance
“…Thus, in a given context, IR practices can be examined to observe whether such practices comply with or contradict the theoretical framework. Fourth, existing IR templates such as King III Report on Corporate Governance for South Africa and the IIRF are mainly based on stakeholder theory (Jayasiri et al, 2022). This study helps to develop new IR templates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in a given context, IR practices can be examined to observe whether such practices comply with or contradict the theoretical framework. Fourth, existing IR templates such as King III Report on Corporate Governance for South Africa and the IIRF are mainly based on stakeholder theory (Jayasiri et al, 2022). This study helps to develop new IR templates.…”
Section: Discussionmentioning
confidence: 99%
“…The primary areas of focus in previous IR studies are IR disclosures, evaluation of IR disclosure practices, and hypothesis testing in relation to the determinants and effects of IR practices, including the adoption of IR and IR disclosure practices. However, after reviewing 210 IR articles published from 2009 to 2020, Jayasiri et al (2022) point out that a large number of IR studies do not use any theories. Hsiao et al (2022) report a similar finding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focus on studies published between January 2013 and April 2023 (when this review was completed) to cover the most recent 10 full years of development in relevant areas. Finally, in line with recent literature review studies and in an attempt to provide timely evidence that would also inform the IAASB, we restrict our sample to studies published in journals that rank B or higher on the Australian Business Deans Council (ABDC) list (Hoque, 2014; Jayasiri et al, 2023; Moses & Hopper, 2022). We provide detailed descriptive statistics of our final sample in the following paragraph and Appendices A, B, and C.…”
Section: Literature Identification Methodologymentioning
confidence: 99%
“…The presence of time-varying amounts of diazinon, propanil etc., in aquatic bodies has been reported in many studies. Jayasiri et al (2022) found that pesticide detection occurs in sporadic peaks linked to their application times. Given the short persistence lifetimes of about a day or less for diazinon and propanil at 30-36 degrees Celsius prevalent in the regions studied, these spikes of pesticide-residues rapidly drop to zero, and fully clear after monsoonal events.…”
Section: Are Pesticide Residues Implicated?mentioning
confidence: 99%